Biomedical Applications of Terahertz Spectroscopy and Imaging. Issue 10 (October 2016) - Yang, Xiang; Zhao, Xiang; Yang, Ke; Liu, Yueping; Liu, Yu; Fu, Weiling; Luo, Yang
Abstract : Terahertz (THz = 10 12  Hz) radiation has attracted wide attention for its unprecedented sensing ability and its noninvasive and nonionizing properties. Tremendous strides in THz instrumentation have prompted impressive breakthroughs in THz biomedical research. Here, we review the current state of THz spectroscopy and imaging in various biomedical applications ranging from biomolecules, including DNA/RNA, amino acids/peptides, proteins, and carbohydrates, to cells and tissues. We also address the potential biological effects of THz radiation during its biological applications and propose future prospects for this cutting-edge technology. Trends: THz spectroscopy has proven to be an innovative tool for providing new insights into the hydration shell in the solvation dynamics of protein solutions. THz in-line digital holography, THz near-field imaging modality, and THz endoscope prototypes have been utilized to identify abnormal tissues faster and more accurately. Increasing applications of artificial modeling and numerical computation are becoming essential supplements for THz biological effect studies.